Factors of migrant children’s participation in basic medical insurance in China: an empirical study based on DEMATEL-ISM method - Li, Hongyan; Yang, Chuanghao; Liu, Zhiyang; Chen, Zhihao (Frontiers in Public Health, 2024)
BackgroundDeepening medical insurance reform is pivotal in promoting fairness, inclusiveness, and sustainability within the system, particularly by enhancing coordination levels and strengthening the interconnection between medical insurance, healthcare, and pharmaceuticals. In China, 71.09 million migrant children, who make up 23.86% of the total child population, exhibit lower participation rates in medical insurance compared to other groups. The health status of children serves as a crucial barometer for the country’s socioeconomic standing and the quality of its medical services. Therefore, the inclusion of migrant children in basic medical insurance is essential for elevating their health standards and contributing to the accumulation of human capital.MethodThis study employed the structural-dynamic-process-result framework derived from synergy theory. It identified 18 factors influencing the participation of migrant children in basic medical insurance. Utilizing the DEMATEL-ISM method, the research analyzed these factors, culminating in the development of a comprehensive five-level hierarchical structure model.ResultThe research identified the medical insurance system’s arrangements as central to influencing the participation of migrant children in medical insurance. The household registration system emerged as a critical factor with significant mandatory and motivational impacts. The study categorized the 18 influencing factors into three tiers: superficial inducing factors, intermediate influencing factors, and deep-rooted causal factors. These tiers demonstrate a complex web of interdependencies and influences, highlighting that encouraging migrant children’s participation in medical insurance is a multifaceted systemic endeavor. This process necessitates collaborative efforts from families, schools, markets, society, and government bodies.ConclusionTo effectively foster the participation of migrant children in basic medical insurance, a strong focus on identifying and addressing core issues is required. This approach should be coupled with enhanced strategic planning and coordination skills to ensure that reforms and developmental strides are equitably beneficial. Recommendations include decentralizing children’s medical insurance from local constraints, refining insurance system design, elevating the level of medical insurance coordination, and boosting insurance participation efficiency. Additionally, fortifying the collaborative dynamics among healthcare, medical insurance, and pharmaceutical sectors is crucial in building a united front to support migrant children’s healthcare needs.